New Evaluation Model: Paem (Public Administration Evaluation Model) - Raluca Antonie (GÂRBOAN) (Transylvanian Review of Administrative Sciences, 2008)
In order to be effective, evaluation should be based on solid monitoring systems. If the monitoring system is missing, what should be done? In this respect, the new model, called PAEM (Public Administration Evaluation Model), is a possibility. It generates structured programs and projects out of mere unstructured activities of public institutions. It helps building an indicator system that has a double functionality: it secures the future existence of a monitoring system and provides a functional evaluation toolkit.